2020
DOI: 10.17932/ejoh.2020.022/ejoh_v02i2003
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Impact of War on Pregnancy in Syrian Refugee Women: A Retrospective Study

Abstract: Objective:The aim of this study was to investigate the perinatal and postpartum results of refugee Syrian pregnant women in Turkey and to evaluate the effect of the war on pregnancy. Material and Methods:In the study, a total of 1020 women applying for pregnancy and giving birth at Bakırkoy Dr. Sadi Konuk Training and Research Hospital, Department of Gynecology and Obstetrics Clinic between the 2014 January-2016 January dates were included, 509 of whom were Syrian refugees and 511 of whom were Turkish. By exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Immigrant women constitute 48% of the world’s immigrants, and they are more vulnerable to psychological disorders due to their different needs during migration and pregnancy [ 10 , 53 ]. In a pilot study conducted in Lebanon, Syrian migrant women were found to show more depression symptoms than Lebanese women [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immigrant women constitute 48% of the world’s immigrants, and they are more vulnerable to psychological disorders due to their different needs during migration and pregnancy [ 10 , 53 ]. In a pilot study conducted in Lebanon, Syrian migrant women were found to show more depression symptoms than Lebanese women [ 23 ].…”
Section: Discussionmentioning
confidence: 99%